CC Chemokine Ligand 20 and Its Cognate Receptor CCR6 in Mucosal T Cell Immunology and Inflammatory Bowel Disease: Odd Couple or Axis of Evil? - Lee, Adrian Y.; Eri, Rajaraman; Lyons, Alan B.; Grimm, Michael; Korner, Heinrich (Frontiers in Immunology, 2013)
Chemokines and their cognate receptors have been identified as major factors initiating and governing cell movement and interaction. These ligands and their receptors are expressed on a wide variety of cells and act during steady-state migration as well as inflammatory recruitment. CCR6 is a non-promiscuous chemokine receptor that has only one known chemokine ligand, CCL20, and is present on B and T cells as well as dendritic cells (DCs). Two CD4+ T cell populations with opposing functions present in the intestines and the mesenteric lymph nodes express CCR6: the pro-inflammatory TH17 and regulatory Treg cells. CCL20 is also present in the intestine and is strongly up-regulated after an inflammatory stimulus. Interestingly, this ligand is also expressed by TH17 cells, which opens up the possibility of autocrine/paracrine signaling and, consequently, a self-perpetuating cycle of recruitment, thereby promoting inflammation. Recently, CCR6 has been implicated in inflammatory bowel disease (IBD) by genome wide association studies which showed an association between SNPs in the genomic region of the CCR6 gene and the inflammation. Furthermore, recent research targeting the biological function of CCR6 indicates a significant role for this chemokine receptor in the development of chronic IBD. It is therefore possible that IBD is facilitated by a disordered regulation of TH17 and Treg cells due to a disruption in the CCL20-CCR6 axis and consequently disturbed mucosal homeostasis. This review will summarize the literature on CCL20-CCR6 in mucosal immunology and will analyze the role this receptor-ligand axis has in chronic IBD.